Conocimientos, prácticas maternas y frecuencia de infecciones respiratorias agudas en niños menores de cinco años - Abanto Arana, Cintya Fiorella (2019)
This study of correlational descriptive type of cross-section, was carried out during the months of June to September 2018 in the Centre of health Santa Lucía de Moche, in order to determine the relationship between the level of knowledge, maternal and practices with frequency of IRAS in children under five years old. The sample was conformed by 141 mothers of children under five years that met the inclusion criteria. The so-called instrument was used: the level of knowledge, practices and TEST frequency of acute respiratory infections in children under five years old (TNCPFIRANM). The information obtained was processed in the program SPSS version 23, and arose in two-way tables. Independence of criteria "Chi-squared" test is used to determine the relationship between variables. Results indicated that the 82.3% of mothers have a level of high knowledge on IRAS, the 87.2% carry out appropriate practices and arises a 55.3% of frequencies of IRAS, being these unacceptable. The results show that there are significant relationship (p=0.012) between maternal knowledge and frequency of IRAS; on the other hand there is no significant relationship (p=0.68) between maternal practices and frequency of IRAS.